Ethnicity and Anxiety: A Psychometric Evaluation of the STICSA. (July 2015) - Lancaster, Steven L.; Melka, Stephen E.; Klein, Keith P.; Rodriguez, Benjamin F.
The current study examined the convergent validity and factor structure of the State-Trait Inventory of Cognitive and Somatic Anxiety in a sample of African Americans and European Americans. Validity analyses revealed similar associations; however, the factor analysis failed to support the original factor structure and factorial variance was consistently demonstrated.